Functional analysis of a chromosomal deletion associated with myelodysplastic syndromes using isogenic human induced pluripotent stem cells - Kotini, Andriana G (Nat Biotechnol, 2015)
Chromosomal deletions associated with human diseases, such as cancer are common, but synteny issues complicate modeling of these deletions in mice. We use cellular reprogramming and genome engineering to functionally dissect the loss of chromosome 7q [del(7q)], a somatic cytogenetic abnormality present in myelodysplastic syndromes (MDS). We derive del(7q)- and isogenic karyotypically normal induced pluripotent stem cells (iPSCs) from hematopoietic cells of MDS patients and show that the del(7q) iPSCs recapitulate disease-associated phenotypes, including impaired hematopoietic differentiation. These disease phenotypes are rescued by spontaneous dosage correction and can be reproduced in karyotypically normal cells by engineering hemizygosity of defined chr7q segments, in a 20 Mb region. We use a phenotype-rescue screen to identify candidate haploinsufficient genes that might mediate the del(7q)- hematopoietic defect. Our approach highlights the utility of human iPSCs both for functional mapping of disease-associated large-scale chromosomal deletions and for discovery of haploinsufficient genes.